Current clinical and translational challenges in temporomandibular joint reconstruction - Baecher, Helena; Maheta, Bhagvat; Lottner, Lisa-Marie; Panayi, Adriana C.; Knoedler, Samuel; Guastaldi, Fernando; Mano, João F.; Koerdt, Steffen; Rendenbach, Carsten; Heiland, Max; Knoedler, Leonard; Doll, Christian (Frontiers in Bioengineering and Biotechnology, 2025)
Total joint reconstruction (TJR) is essential for the management of end-stage temporomandibular joint (TMJ) disorders. Current reconstruction techniques include the use of autologous grafts, such as chondrocostal tissue or fibula, and alloplastic TMJ replacement systems. Commercially available TMJ replacement systems provide both stock and customized prostheses. Advances in computer-aided design/computer-aided manufacturing technology, three-dimensional printing, and virtual surgical planning have accelerated the trend toward individualized TMJ prostheses, enhancing anatomical adaptation, intraoperative efficiency, and postoperative outcomes. A promising alternative under preclinical investigation is TMJ tissue engineering, a regenerative approach utilizing scaffolds, stem cells, and growth factors to reconstruct specific TMJ components, including the skeletal condyle, fibrocartilaginous disc, and glenoid fossa. Bioprinting has further transformed the field by enabling the creation of complex, multi-tissue structures with cellular viability and functionality. Techniques such as integrated tissue and organ printing and volumetric printing have shown promise for enhancing graft performance by improving scaffold heterogeneity. However, these advanced approaches remain in the preclinical stage and require critical evaluation before clinical translation. Despite these advancements, challenges such as high costs, technical complexities, and the need for extensive, robust datasets persist. Continued research into novel biomaterials, advanced biofabrication techniques, and digital surgical technologies, supported by larger preclinical and in vitro studies, is imperative to address these limitations and advance clinical applicability.